Política monetaria y redistribución de la riqueza en el Perú a través de un modelo de agentes heterogéneos, 2002 – 2019 - Menezes de la Cruz, Jose Rodney (2024)
This research examines the distributive effects of monetary policy on the Peruvian economy, using a Dynamic Stochastic General Equilibrium (DSGE) model with heterogeneous agents, calibrated and estimated through Bayesian techniques. The study focuses on analyzing how monetary policy shocks affect the distribution of income, consumption, and wealth among formal and informal households, incorporating the heterogeneity of economic agents and assessing the aggressiveness of monetary interventions. The results show that monetary policy has significant redistributive effects in the Peruvian economy, although these effects are predominantly transitory, with inequality measures returning to their stationary states in the medium term. The main hypothesis that monetary policy shocks significantly impact economic distribution is validated, and it is observed that the aggressiveness of monetary policy modulates the magnitude and speed of convergence towards equilibrium. This research contributes to the growing body of literature that recognizes the importance of considering the heterogeneity of agents and the distributive consequences of macroeconomic policies, especially in economies with high levels of heterogeneity like Peru and emerging economies.